THE INFLUENCE OF SOCIAL MEDIA INSTAGRAM TOWARD PURCHASE DECISION MAKING PROCESS IN ORGANICSUPPLYCO - Maidi Helinsha (Jurnal Manajemen dan Bisnis Madani, 2021)
This research was motivated by the increasing of internet and digital era in communication, especially in online shopping. Changes in the way of communicating are through social media. Not only used as virtual relationship communication, social media is also used as an online shopping platform, especially Instagram social media. The shift of communication through social media led to a shift in the way consumers shop, by utilizing features and content that is on Instagram social media. The shift in shopping is influenced by consumer’s purchase decision making processes, both internally and externally. The purpose of this research is to show that internal and external factors cannot be separated from purchasing decision making process because it is integral so that it is reflective of OrganicsSupplyCo, sellers can understand what internal and external factors that have a big influence for consumers in online shopping through Instagram. By mirroring OrganicSupplyCo, an online shop can create online campaigns and activities that are in accordance with the needs and desires of consumers. The research was conducted in May to August 2018. This research using quantitative in questionnaire. The result of this research showed that Instagram internal and external factors influence OrganicSupplyCo’s consumer in purchasing decision making process. The internal factor are content quantity and content quality. The external factors are instastories and photoshare.